PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KOTA TANGERANG SELATAN - Ilmi, Fatihah Nurul; Ludvy, Achmad (Journal of Research and Publication Innovation, 2024)
The aim of this research is to find out how much influence work discipline and the physical work environment have on employee performance at the South Tangerang City Environmental Service. The method in this research uses quantitative methods with a purposive sampling technique totaling 75 respondents. Data analysis techniques use data instrument tests, classical assumption tests, multiple linear regression, coefficient of determination. Hypothesis testing in this study used the t test and F test. Based on the research results, work discipline has a significant effect on employee performance with a coefficient of determination value of 0.396, meaning that employee performance is influenced by work discipline and the physical work environment by 39.6% and the remaining 60. .4% is influenced by other factors. This has been proven by the t test, the calculated t value > t table or (3.007 > 1.993) is confirmed by the p value < sig 0.05 or (0.000 < 0.05) thus H01 is accepted and Ha1 is rejected, this is shows that there is a significant influence between discipline on employee performance. The results of this research show that there is a positive influence between work discipline variables and the physical work environment simultaneously, where the multiple linear regression equation Y = 13.441 + 0.312X1 + 0.390X2 means a positive effect. This is proven by the results of the F test hypothesis test which obtained the calculated F value > F table or (23.599 > 3.124). This is reinforced by the p value Sig. 0.05 or (0.000 < 0.05), which means that it can be concluded that the variables of work discipline and physical work environment have a significant effect on employee performance.